Evaluating Social Protection Programs in Tajikistan - Hyun H. Son (Asian Development Bank (ADB), 2011)
Following independence from the former Soviet Union, Tajikistan inherited an extensive social protection system that included a range of cash and noncash benefits. While the economy is well into its transition from a centrally planned to a market-oriented economy, its social welfare policies still adhere to the methods and approaches of the Soviet period. This is true for social protection, which has both social insurance and social assistance components, and for which benefits are effectively noncontributory in nature in that no contributions are collected from employees. In this paper, we examine the performance of the country's social protection system - essentially public transfers for the elderly and disabled - in terms of reducing poverty, with the aim of identifying its key problems. Since the government provides such public transfers mainly as pensions (i.e., old-age pension, disabled pension, and survivors pension), it merits an in-depth analysis of whether or not these transfer programs reach the intended beneficiaries; that is, how well do they target the intended beneficiaries? Using data from the Living Standards Measurement Survey conducted in 2007, the study finds that only 43% of poor households are receiving transfers from the government, while 33% of nonpoor households receive transfers. This study argues for applying a targeted approach to public transfer programs, including noncontributory pension schemes aimed at the most vulnerable populations.
hdl:11540/2011
Keywords: 330; Armutsbekämpfung; Öffentliche Sozialleistungen; Wirkungsanalyse; Tadschikistan